Advocating for a change of mentality in the development of metadata standards: historical celestial cartography as a specialization example - Elena Escolano Rodríguez; M. Pilar Alonso-Lifante; Francisco Javier Molero; Donatella Randazzo (JLIS.it, 2017)
We live in a highly volatile technological environment, in which the generation of new data and information access tools has increased the level of specialization of the users’ information needs. In this changeable scenario, standards and the role of librarians must also evolve along with the services provided to users. The lack of specialization in standards is leading librarians to improvise local solutions when cataloguing specialized resources, thus failing to benefit global interoperability among libraries, and with other institutions and initiatives. As different cataloguing standards, as well as many conceptual models, point out the necessity to deal with the specific users’ needs, the main goal of this paper is to advocate for meeting those needs through the development of metadata standards. In particular, our methodology consists in showing and explaining the needs of a particular type of users (astronomers and astrophysicists) and proposing the inclusion in the standards of elements important for the description of historical astronomical resources. Through an example, we show not only the feasibility of application of these elements, but also how the enhancement of the level of specialization of the standards, and therefore of the records made under their rules, can definitely contribute to a global solution for a much improved scientific information retrieval.